Profitability in Linking Governance Structure and Firm Value - Dini Wahjoe Hapsari; Budiharjo, Roy; Pratomo, Dudi; Yazid, Hanif (Fakultas Ekonomi dan Bisnis Universitas Tarumanagara, 2025)
The governance structure of SOEs is distinctive, with board directors managing while the audit committee, independent commissioners, and shareholders supervise. This study evaluates SOEs' success by analyzing profitability as a mediator between corporate governance and firm value. The study focused on SOEs listed on the Indonesia Stock Exchange (IDX) from 2019 to 2023, with 100 data observations obtained via purposive sampling. Panel data analysis revealed that the audit committee, independent commissioners, and institutional ownership significantly influence profitability. However, board directors do not significantly impact profitability or firm value, and overall governance structure does not notably affect firm value. Profitability mediates the effects of the audit committee, independent commissioners, and share ownership on firm value but not the directors’ influence. These results indicate that the government's role as the largest shareholder heavily influences the determination and role of board directors in SOEs.